If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3g + -7 = -7 + -2g Reorder the terms: -7 + -3g = -7 + -2g Add '7' to each side of the equation. -7 + 7 + -3g = -7 + 7 + -2g Combine like terms: -7 + 7 = 0 0 + -3g = -7 + 7 + -2g -3g = -7 + 7 + -2g Combine like terms: -7 + 7 = 0 -3g = 0 + -2g -3g = -2g Solving -3g = -2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2g' to each side of the equation. -3g + 2g = -2g + 2g Combine like terms: -3g + 2g = -1g -1g = -2g + 2g Combine like terms: -2g + 2g = 0 -1g = 0 Divide each side by '-1'. g = 0 Simplifying g = 0
| 33-x=26 | | 7x+10=6x+17 | | -(x+3)+6x= | | 23-x=17 | | 9x^2-17=-16 | | -7(1+4x)=217 | | 6x+9=4x+25 | | 8-7j=-6j | | 12+1y+3y=28 | | (2x-1)/3=5x-6/4 | | 2x-9=3x+0 | | 4=-2(4.50+25p) | | -32-8x+6x=12 | | -3(w+1)-4= | | 58=3x+4x+2 | | p=5+2q | | 4=-2(4.50+25) | | 3X*2-12X=2X+7 | | 19+169r^2=380 | | 2.1x-2.16=0.84-5.4 | | 5w=6w-8 | | 5x+2x-6=43 | | 3(2u-3)-2(u+4)= | | 5p^2-17=28 | | f(x)=x-26 | | -400=8(-8b+6) | | 9(-39/2)-5((-39/2)-6) | | 5(w+6)-7w= | | 5x/5x^3 | | 9(-39/2)-5((-39/2)-6 | | 7v^2-3=4 | | -7x+9-4x=130 |